The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/jsbed-03-2017-0083
|View full text |Cite
|
Sign up to set email alerts
|

Exploring entrepreneurial intention’s mediating role in the relationship between self-efficacy and nascent behaviour

Abstract: Purpose The purpose of this paper is to examine the mediating role of entrepreneurial intention (EI) in relation to the influence of the five dimensions of entrepreneurial self-efficacy (ESE) on nascent behaviour. Design/methodology/approach The study relies on a quantitative approach where primary data were collected from 294 final year undergraduate students at a public university in Zambia. The data were examined by using correlation, logistic regression and mediation analyses. Findings The findings ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 72 publications
4
29
1
Order By: Relevance
“…This response rate is impressive and confirms Saunders and Lewis' (2012) argument that the face-to-face approach is usually associated with high response rate. The response rate is also comparable to previous student research studies (e.g., Mwiya et al, 2018). The sample profile is given in table 1 below.…”
Section: Methodology 31 Sample and Data Collectionsupporting
confidence: 78%
See 2 more Smart Citations
“…This response rate is impressive and confirms Saunders and Lewis' (2012) argument that the face-to-face approach is usually associated with high response rate. The response rate is also comparable to previous student research studies (e.g., Mwiya et al, 2018). The sample profile is given in table 1 below.…”
Section: Methodology 31 Sample and Data Collectionsupporting
confidence: 78%
“…The majority of the respondents were aged between 21 and 25. The average age of between 21 and 25 in the sample is typical of university students in Zambia (Mwiya, et al, 2018). 46% of the respondents were from the School of Business while School of Natural Resources had the least respondents (4%).…”
Section: Methodology 31 Sample and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] Finally, intention can predict individual behavior, so understanding the factors forming EI will provide insight into the process of business creation (Galanakis, and Giourka, 2017). [26] Thus, an intention-based model offers a lot of entrepreneurial research because entrepreneurial activity is planned behavior and the intended understanding can help detect potential actions.…”
Section: Entrepreneurial Intentions (Ei)mentioning
confidence: 99%
“…Similarly, Tsai et al (2016) found that individual attitudes towards entrepreneurship influenced the relationship between ESE and EI. ESE is positively and significantly related to EI (Bruce, et al, (2018). [72] Therefore, the hypothesis proposed is:  H 5 : Entrepreneurial self-efficacy (ESE) influences entrepreneurial intentions (EI)…”
Section: Entrepreneurial Self-efficacy (Ese)mentioning
confidence: 99%